Pengaruh Lingkungan Tempat Tinggal Dan Karakteristik Rumah Tangga Terhadap Munculnya Pekerja Anak Di NTT (Analisis Data Susenas Dan Potensi Desa 2011) - Ardana, I Made Juli; Arjana, I Gusti Bagus; Ramang, Ruslan (Bumi Lestari, 2016)
In Nusa Tenggara Timur the appearance of child labour affected by the living environment and the household characteristic. The descriptive analysis showed that in 2011 there were 4,37 % child labour in NTT. The inference analysis showed the probability of children who live in urban area become a child labour was 0,56 times than who live in rural area, the probability of children who live in a region that there was school available become a child labour is 0,43 times than children who live in a region without school. Children with head of household work in formal sector had less probability become a child labour than children with head of household not working/work in informal sector, the probability was 0,47 times. Probability of children with head of household education highschool or above become a child labour 0,58 times than children with head of household education secondary school or less. Probability of children with head of household sex was male become a child labour 0,70 times then whose head of household sex was female. A boy have probability become a child labour 1,36 times than a girl. This result showed that living environment and household characteristics influence the appearance of child labour in NTT.
Keywords: environment; child labour; household characteristics; logistic regression